2021
DOI: 10.3390/rs13163068
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Subsurface Processes in Land Surface Modeling over a Temperate Region: An Analysis with SMAP, Cosmic Ray Neutron Sensing and Triple Collocation Analysis

Abstract: Land surface models (LSMs) simulate water and energy cycles at the atmosphere–soil interface, however, the physical processes in the subsurface are typically oversimplified and lateral water movement is neglected. Here, a cross-evaluation of land surface model results (with and without lateral flow processes), the National Aeronautics and Space Administration (NASA) Soil Moisture Active/Passive (SMAP) mission soil moisture product, and cosmic-ray neutron sensor (CRNS) measurements is carried out over a tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…The CRNS footprint covers up to 18 ha with a measurement depth of up to 80 cm (Bogena et al., 2015; Köhli et al., 2015; Zreda et al., 2008). The continuous development of CRNS technology has enabled SM monitoring under a variety of climatic conditions, which has promoted its application in hydrological modeling (R. Baatz et al., 2017), satellite product validation (Zhao et al., 2021), extreme weather event (drought and flood risk) assessment (Bogena et al., 2022), ecohydrological (e.g., snow, precipitation, and vegetation) monitoring (Bogena et al., 2020), and agricultural management (Li et al., 2019). The advantages of CRNS have made it increasingly attractive, and large‐scale CRNS networks have been established in Europe, the USA, Australia, and India for large‐scale soil moisture monitoring with high temporal resolution, which can also benefit the multifaceted hydrological applications mentioned above.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CRNS footprint covers up to 18 ha with a measurement depth of up to 80 cm (Bogena et al., 2015; Köhli et al., 2015; Zreda et al., 2008). The continuous development of CRNS technology has enabled SM monitoring under a variety of climatic conditions, which has promoted its application in hydrological modeling (R. Baatz et al., 2017), satellite product validation (Zhao et al., 2021), extreme weather event (drought and flood risk) assessment (Bogena et al., 2022), ecohydrological (e.g., snow, precipitation, and vegetation) monitoring (Bogena et al., 2020), and agricultural management (Li et al., 2019). The advantages of CRNS have made it increasingly attractive, and large‐scale CRNS networks have been established in Europe, the USA, Australia, and India for large‐scale soil moisture monitoring with high temporal resolution, which can also benefit the multifaceted hydrological applications mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al. (2021) compared the CRNS data with simulated soil moisture using both the land surface model Community Land Model (CLM, version 3.5) and a coupled land surface‐subsurface model (CLM‐ParFlow). They found that the coupled model simulations showed less bias and reproduced better soil moisture dynamics than the CLM stand‐alone, demonstrating the importance of considering lateral subsurface flow in subsurface hydrological simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation